Triangle Syariah Justice Ecosystem: Constructing Business Model of Pension Fund - Huda, Fahmi Alamil; Kurnia, Andiyani (Universitas Islam Internasional Indonesia, 2022)
The objective of this paper is to redesign the Indonesian pension fund's business model and management system, and develop new strategies to balance profits, affordability, and sustainability. The authors consider the Malaysian pension system and adapt the INTERDAP application used by PT. Angkasa Pura II. Through this qualitative case study, we apply the foundations of the Triangle Syariah Justice Ecosystem (TSJE) to digitize the pension system and support green investment in the long run by modeling the business strategy, facilitating the business model and supplier relationship management, and creating mutually beneficial management among stakeholders. The study found that Malaysia's pension system has an investment purpose, while that of Indonesia only provides pension loans based on previously agreed cumulative contributions. Malaysia encourages people across the country to save on severance funds, and the pension system is still managed conventionally. Malaysia requires a pension contribution of 23 percent of the employee's base salary, while Indonesia requires a meagre 3 percent. This affects the contribution of pension funds to Gross Domestic Product (GDP), with Malaysia's pension fund accounting for 60 percent of GDP but Indonesia’s accounting for only 6 percent. The authors also consider that to become a developed country, pension funds need to reach 60 percent of GDP by 2045, because 42 percent of the total supply of funds in the infrastructure sector originates from pension funds. The practical implications of this study are on access to information, security, and transparency in the management of pension funds through a digital system supervised by the Syariah Regulator, alongside the Indonesian government's efforts to realize support for the green economy.